Video Animation: Improving Older Adults Patients Knowledge and Motivation Related to Hypertension Diet - Gusti Ayu Kade Budiarti; Sri Susanty; Ruslan Madjid; Ramadhan Tosepu (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
Hypertension is a dangerous medical condition that can increase the risk of heart, brain, and renal problems, among other issues. A balanced diet is an essential hypertension control intervention. This study seeks to examine the efficiency of employing animation media to explain the application of diets that prevent hypertension and boost the understanding and motivation of senior patients at Bahteramas Regional General Hospital. In both the control and intervention groups, a quantitative-quasi-experimental design was adopted, with pre-test and post-tests. Data was obtained via questionnaires from 92 respondents chosen using a purposive sampling approach, with 46 in the intervention group from the cardiac clinic and 46 in the control group from geriatric clinic. The data were analyzed using the paired t-test. The findings of the study indicated that patient knowledge increased significantly (p = 0.007) in the cardiac clinic following the administration of animation media, whereas in the geriatric clinic, no impact was observed (p = 0.000). Patient motivation increased significantly in the cardiac clinic following the administration of animation media (p = 0.003) and in the geriatric clinic in the absence of intervention (p = 0.000). There was no significant difference between the two groups in pretest knowledge (p = 0.666) and motivation (p = 0.747); however, there were significant differences in posttest knowledge (p = 0.015) and motivation (p = 0.026). Patient knowledge was affected by animation media in the cardiac clinic (p = 0.007) and without therapy in the geriatric clinic (p = 0.000). Incorporating animated educational content into routine patient counseling and health education programs can be beneficial in the future. Keywords: animation media, hypertension diet, knowledge, motivation, video Abstrak Video Animasi: Meningkatkan Pengetahuan dan Motivasi Pasien Lanjut Usia untuk Diet Hipertensi. Hipertensi adalah kondisi medis berbahaya yang dapat meningkatkan risiko masalah jantung, otak, ginjal, dan masalah lainnya. Pola makan yang baik sangat penting sebagai intervensi pengendalian hipertensi. Tujuan penelitian ini adalah menguji efisiensi penggunaan media animasi untuk menjelaskan penerapan diet hipertensi dan meningkatkan pemahaman dan motivasi pasien lanjut usia di Rumah Sakit Umum Daerah (RSUD) Bahteramas. Pada kelompok kontrol dan perlakuan, desain quantitative-quasi-experimental diadopsi, dengan pre-test dan post-test. Data diperoleh melalui kuesioner dari 92 responden yang dipilih dengan pendekatan purposive sampling, terdapat 46 orang pada kelompok intervensi di klinik jantung dan 46 orang pada kelompok kontrol di klinik geriatri. Data dianalisis menggunakan paired T-test. Temuan penelitian menunjukkan bahwa pengetahuan pasien meningkat secara signifikan (p = 0,007) di klinik jantung setelah pemberian media animasi, sedangkan di klinik geriatri, tidak ada intervensi yang diamati (p = 0,000). Motivasi pasien meningkat secara signifikan di klinik jantung setelah pemberian media animasi (p = 0,003) dan di klinik geriatri tanpa adanya intervensi (p = 0,000). Tidak terdapat perbedaan yang signifikan antara kedua kelompok pada pengetahuan pre-test (p = 0,666) dan motivasi (p = 0,747); Namun terdapat perbedaan yang signifikan pada pengetahuan post-test (p = 0,015) dan motivasi (p = 0,026). Pengetahuan pasien dipengaruhi oleh media animasi di klinik jantung (p = 0,007) dan tanpa terapi di klinik geriatri (p = 0,000). Menyertakan konten edukasi animasi dalam rutinitas konseling pasien dan program pendidikan kesehatan dapat memberikan manfaat di masa depan. Kata Kunci: diet hipertensi, media animasi, motivasi, pengetahuan, video